Prenatal Diagnosis of the Duchenne Muscular Dystrophy. A Family Presentation - Humberto Perera Navarro; Tatiana Zaldivar-Vaillant; Carlos Viñas-Portilla; Ariel Medina Concepción; Rosa Guerra Badía; Mariesky Zayas Guillot (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
The Duchenne muscular dystrophy is one of the most frequent hereditary myopathies that exist. It is characterized by degeneration of the muscle skeletal fibers which produce handicap in the first decade of life bringing about death due to cardiac or respiratory failure. The responsible gene of the disease is known as DMD and it is located in the X chromosome shorter arm. A family history is presented in which the pregnant woman who is the sick patient's sister asks for a prenatal diagnosis. An indirect molecular study was performed with the STR-50 polymorphic marker. After the analysis of the results in which the lab methodology was applied, the fetus was found to be sick and the family decided to interrupt the pregnancy.